Reality of Using Blackboard Learning System at Applied College in Saudi Arabia - Alharbi, Ibrahim Bader A.; Elnagar, Ahmed K.; Abotaleb, Siham A.; Elzoghbi, Hend M. (Journal of Applied Science, Engineering, Technology, and Education, 2022)
This research aims to study the reality of using e-learning systems in the educational process, in addition to analyzing the use of the BbS examining the decisions of THP and weighing its advantages and disadvantages. The descriptive technique was used in the investigation. The field study was carried out with the use of a questionnaire distributed to students enrolled in the THP at the Applied College, Al-Ula Branch. SPSS 25 was used to do a statistical analysis of the gathered data. The study's found that students in the THP utilize the Bbs functionalities to study their courses, resulting in a low degree of benefit from the Bbs. The study proposes that seminars and training courses be held for course teachers and students to train them on the BbS, encouraging instructors to utilize the range of evaluation tools offered by the BbS, including assignments, brief and oral exams, periodic exams, and final exams